Pendampingan Pengelolaan Limbah Rumah Tangga Guna Mewujudkan Zero Waste Society di Desa Purwojati Kabupaten Mojokerto - Wahyuningtyas, Neni; Rosyidah, Yuniar; Defandiari, Wahyu Rio (JPM (Jurnal Pemberdayaan Masyarakat), 2024)
This mentoring program outlines strategies and concrete steps implemented to overcome household waste management problems in Purwojati Village, Ngoro District, Mojokerto Regency. This problem is motivated by the lack of knowledge and skills of the community in managing waste into valuable products. Therefore, the UM Abdimas Team provides waste processing assistance to residents, Community Self-Help Groups, and the Purwojati Village Government by maximizing the use of waste management tools provided. As a result, residents can independently process household waste into eco-enzymes, compost and various handicrafts. So it can reduce the volume of waste in Mojokerto Regency, prevent environmental pollution, and create a new source of income for the residents of Purwojati Village. This program also supports the Zero Waste Society vision which aims to create a society that is more responsible for their environment, especially in Purwojati Village.